Analisa Konsep Rechterlijk Pardon Dalam Proses Mediasi Perkara Diversi - Yulian Effendi; Zulkarnain; M. Syahzilli; Henky Irawan; Novandro Ari Sekentianda (Lex Stricta : Jurnal Ilmu Hukum, 2024)
Criminal prosecution is the process of determining and imposing penalties under criminal law. In cases of minor criminal offenses, settlement of cases through reconciliation is permitted. This reconciliation involves the victim, the perpetrator, and the community, but its practice remains limited and is typically conducted outside of court. Forms of reconciliation may include compensation for losses and granting forgiveness, which can influence the leniency of the sentence imposed on the perpetrator. Under Articles 364, 373, 379, 384, 407, and 483 of the Criminal Code, minor criminal offenses that can be resolved through mediation are punishable by a maximum prison sentence of 3 months or a maximum fine of Rp2.5 million. In the juvenile criminal justice system, the diversion mechanism already accommodates this reconciliation. The hope is that victims and offenders can jointly seek the best solution, thereby giving the practice of reconciliation clear legitimacy within Indonesia's criminal justice system.